Correspondence of Prior Knowledge with Information Seeking Behavior of Graduate Students in Tehran University - Mahmood Khosrowjerdi; Mohammad Iranshahi (Iranian Journal of Information Processing & Management, 2009)
Information seeking behavior and its various aspects had been the focus of attention by many researchers around the world. It has been tried and tested in many disciplines. Furthermore, its correlation with many variables such as gender, discipline, occupation, individual knowledge, personality, experience as well as specialization has been measured and had furnished useful results. The present investigation has tested and analyzed the correlation between information seeking behavior and prior knowledge among students enrolled in University of Tehran Graduate Program at both Masters and PhD level. Findings indicate that there exists a positive significance between these two variables. There had been, however, a negative correlation between time as a barrier with affirmation of prior knowledge. The findings are compatible with some prior investigations while incompatible with other s .